2013
DOI: 10.3892/ol.2013.1750
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland tumors: A 20-year review of clinical diagnostic accuracy at a single center

Abstract: Obtaining reliable pre-operative diagnosis is crucial in planning treatment for patients with salivary gland tumors. The purpose of this study was to evaluate the accuracy of pre-operative clinical diagnosis of salivary gland tumors managed at a single tertiary university hospital over a period of 20 years. A retrospective analysis of the period between 1992 and 2011 was carried out to review the cases of patients with salivary gland tumors. A total of 101 patients were enrolled and general data were described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Four out of six cases that presented with pain in our study were diagnosed as malignant by histopathology and similar presentations had been reported by others. 17 A good clinical concordance observed in our study supports a strong clinical history. Other studies had also reported clinical accuracy of 100% and 57% for diagnosing benign and malignant cases respectively 17 though others had reported that no single feature or group of features led to clinical diagnosis of a specific tumor type.…”
Section: Discussionsupporting
confidence: 86%
“…Four out of six cases that presented with pain in our study were diagnosed as malignant by histopathology and similar presentations had been reported by others. 17 A good clinical concordance observed in our study supports a strong clinical history. Other studies had also reported clinical accuracy of 100% and 57% for diagnosing benign and malignant cases respectively 17 though others had reported that no single feature or group of features led to clinical diagnosis of a specific tumor type.…”
Section: Discussionsupporting
confidence: 86%
“…However, the sensitivity and accuracy of FNAC in the detection of malignant characteristics in Ca ex PA are 60% and 46%, respectively[10]. Another retrospective study confirmed that clinical judgment of benign and malignant tumors in the submandibular gland had a low accuracy of 67%[11], so intraoperative frozen section analysis results were particularly important in determining the extent of surgical resection. Unfortunately, there was no accurate diagnosis made before surgery on our patient, so it can only be diagnosed by the intraoperative frozen section analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cleavage of Bid has been established as a linker of both apoptotic pathways, therefore compounds able to induce Bid cleavage and activate caspase 8 on one side as well as cytochrome c release and caspase 9 on the other side, represent synergistic mediators of extrinsic and intrinsic apoptotic event. Here we should mention celastrol (55) [239], sulphoraphane (85) [240] or quercetin (12) [241].…”
Section: Rhus Vernicifluamentioning
confidence: 99%